Teachers' Readiness to Develop Students' Moral Concepts in Innovative Educational Contexts - Leila T. Potanina; Julia V. Koinova-Zoellner; Tatyana V. Sklyarova (National Research Mordova State University, 2020)
Introduction. The development of students' moral beliefs about the world is an essential component in the process of moral education. Various issues concerned with the transmission of moral and ethical values across generations are investigated in the theory and practice of vocational education. However, the problem of teachers' value perceptions about the world as a means of developing students' value systems has attracted little research attention. For the first time, this study aims to identify the levels of teachers' value perceptions about the world as their most important competence in developing students' moral beliefs. Materials and Methods. The research sample included 216 teachers from different regions of the Russian Federation. On the basis of a review of available scientific publications, a theoretical analysis and systematization of Russian and foreign experience in the moral and ethical development of school-age students was carried out. The empirical research consisted in a survey aimed at revealing the respondents' attitude towards improvement of their professional competencies in the field of moral and ethical education. The teachers' value perceptions about the world were identified using two series of the projective technique "Incomplete sentence...". Results. The conducted empirical research confirmed the hypothesis that teachers' competence in implementing the moral and ethical education of schoolchildren is based on their existing value systems. An analysis of the respondents' beliefs about objects and facts of reality from the standpoint of their own value system allowed two levels of value perceptions to be revealed: value-associative and meaning-generating, which differ in the nature of the moral categorization of objects and phenomena of the world. Discussion and Conclusion. The study confirmed the significance of teachers' professional and personal competences in developing students' moral and ethical values. The findings can be of interest for teachers, tutors, psychologists, professors and those investigating various aspects of the process of forming students' moral values.